Vaginal Wall Endometriosis Treated by Low-Dose Estrogen-Progestin: A Case Report. Issue 4 (October 2014) - Murakami, Makoto; Ichimura, Tomoyuki; Kasai, Mari; Kawamura, Naoki; Sumi, Toshiyuki
As vaginal wall endometriosis is rare, standard therapy has not yet been established. We report here a case of vaginal wall endometriosis that was reduced through administration of low-dose estrogen-progestin (LEP). The patient was a 37-year-old woman who presented with atypical genital bleeding (AGB) and dysmenorrhea. We recognized small hematomatous lesions on the posterior fornix of the vagina and a 3-cm mass in the pouch of Douglas, and we diagnosed the patient with vaginal wall endometriosis. We administered drug therapy with LEP. AGB stopped, and both the hematomatous vaginal wall lesion and the mass in the pouch of Douglas were reduced in size. The vaginal and pouch of Douglas lesions did not grow, and both AGB and dysmenorrhea did not appear for 42 months. LEP reduces vaginal wall endometriosis and rectovaginal endometriosis. In this case, we confirmed the direct effect of LEP on a vaginal wall endometriosis lesion. LEP therapy may be effective as postoperative therapy for vaginal wall endometriosis.